The style of the Regent of Madiun in developing the Indonesian Pesilat Village in Madiun Regency - Dony Adi Saputra (Al-Makki Publisher, 2023)
Departing from the plurality of silat universities and frequent conflicts between silat universities in the Madiun area. The Regent of Madiun created a new legalized identity, namely Madiun Regency